Comparative HPLC Evaluation of the Effect of Roasting and Deep Frying Cooking on Vitamins Content of Unripe Plantain (Musa x paradisiaca) - Omolola, Omotosho E. (Covenant Journal of Physical and Life Sciences, 2015)
Musa x paradisiacal (plantain) is among the major tropical staple foods. This study was designed to compare roasting and deep frying method cooking plantain. The fat soluble vitamins constituent of unripe plantain was determined fried with three different oils (canola oil, soya oil and vegetable oil). The vitamins content were determined using High Performance Liquid Chromatography. Roasted plantain samples gave a higher value of vitamins A (0.08 ± 0.01mg/g), D (0.02 ± 0.01mg/g), E (0.01 ± 0.00mg/g) and K (0.05 ± 0.00mg/g) compared to plantain samples fried with canola oil which gave low level of vitamin D (0.03 ± 0.00mg/g), E (0.25 ± 0.00mg/g) and K (0.03 ± 0.00mg/g). However, canola oil gave a very high level of vitamin A (0.72 ± 0.02mg/g). The result showed that roasting plantain in oven retains the vitamin contents compared to deep fat frying. Canola oil is recommended for frying although soya oil can also be used. Key words: Plantain, Roasting, Deep-frying, Fat soluble vitamins, Canola oil, Soya oil.